Spatial Crime Forecasting: Application of Risk Terrain Modeling in a Metropolitan County - Clubb, Audrey (2017)
The present study utilizes a novel approach to spatial crime analysis known as Risk Terrain Modeling (RTM) to assess the applicability of this technique in the prediction of predatory violent crime (homicide, aggravated assault, and pedestrian robbery). RTM provides a methodology for analyzing potential correlates of crime in a spatial context to identify specific locations at the highest risk for crime in the future. The intent of this process is to allow police and other community agencies to identify places at the highest risk for crime to allocate additional resources to stave off potential crime problems. The present study applies this technique to a metropolitan county near Atlanta, Georgia. RTM models were generated for each year from 2010 through 2014 based on several area characteristics including physical and social disorder, criminal elements, risky places, socioeconomic conditions, and area economic health. These models are then tested for their predictive validity and discrimination capabilities. The results indicate that the RTM methodology was successful in identifying many areas of risk for future crime, but was limited in the ability to accurately pinpoint areas at the highest risk of crime. The explained variance in the distribution of crime relative to risk was minimal and the RTM models incorrectly identified many places as high risk that were not subject to future crime while not identifying many areas that did experience crime. While this methodology shows promise on principle, more research is needed to improve performance of the RTM model prior to its use as a potential tool for crime prediction and intervention